2012
DOI: 10.1002/smi.2464
|View full text |Cite
|
Sign up to set email alerts
|

Applying the Stress and ‘Strength’ Hypothesis to Black Women's Breast Cancer Screening Delays

Abstract: Associations between stress and breast cancer highlight stressful life events as barriers to breast cancer screening, increased stress due to a breast cancer scare or diagnosis, or the immunosuppressive properties of stress as a risk factor for breast cancer occurrence. Little is known, however, about how women’s reactions to stressful life events impact their breast health trajectory. In this study, we explore how reactions to stressors serve as a potential barrier to breast cancer screening among Black women… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
52
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 37 publications
3
52
0
Order By: Relevance
“…Although many studies have assessed the relationship between the incidence of breast cancer and life events, both epidemiologically and etiologically, the results have been inconsistent [35-37]. Several of these studies reported that life events were significantly associated with breast cancer risk [37,38]. Evidence has emerged showing that these life events may affect the hypothalamic-pituitary-adrenal axis, resulting in endocrine system disorders, increased cortisol concentrations, and reductions in antineoplastic activity [7,8,39].…”
Section: Discussionmentioning
confidence: 99%
“…Although many studies have assessed the relationship between the incidence of breast cancer and life events, both epidemiologically and etiologically, the results have been inconsistent [35-37]. Several of these studies reported that life events were significantly associated with breast cancer risk [37,38]. Evidence has emerged showing that these life events may affect the hypothalamic-pituitary-adrenal axis, resulting in endocrine system disorders, increased cortisol concentrations, and reductions in antineoplastic activity [7,8,39].…”
Section: Discussionmentioning
confidence: 99%
“…African-American women have often adopted a behavioral script of "strength," encompassing self-reliance, self-sacrifice, and self-silence, to enhance survival in racist and sexist contexts that have existed over generations in the USA (Black & Peacock, 2011). The caregiving roles of many African-American women can result in complex patterns of adaptation, whereby they take on the needs of others while minimizing, neglecting, or postponing personal needs and self-care (Black & Peacock, 2011;Black & Woods-Giscombé, 2012;Carthron, Bailey, & Anderson, 2014;Carthron, Johnson, Hubbart, Strickland, & Nance, 2010;Samuel-Hodge, Skelly, Headen, Carter-Edwards, 2005;Woods-Giscombé, 2010).…”
Section: Introductionmentioning
confidence: 98%
“…Research on the nuanced experiences of life stressors among Black women suggest that Superwoman Schema, or perceived obligations to present an image of strength, suppress emotions, resist support from others, achieve success with inadequate resources, and prioritize caregiving over self-care can adversely affect health-promoting behaviors and HRQOL [35, 37]. Moreover, Network Stress, or the stress experienced by Black women as a result of life challenges experienced by family members and friends [36], might magnify ways in which stress negatively influences aspects of HRQOL in this population.…”
Section: Introductionmentioning
confidence: 99%